2014
DOI: 10.1175/jas-d-14-0001.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Large-Scale Conductivity Inhomogeneities in the Atmosphere on the Global Electric Circuit

Abstract: Theoretical estimation of the influence of large-scale conductivity inhomogeneities on the global electric circuit and, in particular, on the ionospheric potential is considered. A well-posed formulation of this problem is presented, on the basis of which an approximate method is developed so as to take account of large-scale conductivity inhomogeneities. Under certain restrictions imposed on the distributions of the conductivity and the external current density, explicit approximate formulas for the ionospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
(46 reference statements)
2
21
0
Order By: Relevance
“…However, the reduction of conductivity inside the thundercloud can be different due to electrification processes. The effect of reduction of conductivity inside the thundercloud on ionospheric potential created from a thundercloud current dipole was recently studied by Slyunyaev et al [, Figure 5]. In our work the reduction of conductivity by a factor of 20 is used as a representative value.…”
Section: Numerical Model Formulationmentioning
confidence: 94%
See 4 more Smart Citations
“…However, the reduction of conductivity inside the thundercloud can be different due to electrification processes. The effect of reduction of conductivity inside the thundercloud on ionospheric potential created from a thundercloud current dipole was recently studied by Slyunyaev et al [, Figure 5]. In our work the reduction of conductivity by a factor of 20 is used as a representative value.…”
Section: Numerical Model Formulationmentioning
confidence: 94%
“…A full three‐dimensional model [ Bayona et al , ], based on coupling of the continuity equation and Poisson's equation (denoted as CPM in section 2), incorporates the best horizontal resolution of 40 km. Recently, Slyunyaev et al [] compared ECM with results obtained from steady state CPM and found very good agreement under restriction that the height of the atmosphere is much smaller than the horizontal scales of the distributions of the conductivity and the external current density. Slyunyaev et al [] showed also a disagreement between ECM and CPM for horizontal scales of 5 km.…”
Section: Analytical Theorymentioning
confidence: 97%
See 3 more Smart Citations